Teaching the Spanish Civil War in the Basque Country with Historical Comics: a proposal for secondary education (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The present article offers an intervention proposal for teaching the Spanish Civil War in the Basque Country through comic books for students of history at the second course of Bachillerato. To this end, it first examines the contributions by various authors who have viewed the usefulness of graphic novels in the history classroom in a positive manner. More specifically, this article draws upon the recent scholarly works published in the United States about the didactic value of comic books in the history classroom. It later designs a didactic proposal for teaching the Civil War in the Basque Country for students in Spanish History Class in the second year of high school. This study suggests using the historical comic book Gabai. La guerra de Euskadi (1990) by Rafael Castellano and Juan Carlos Nazabal as a means to help students build the capacities to identify, contextualize, and corroborate.
Keywords: Didactics of History; teachers training; critical thinking; graphic novel; secondary education